Visual Evaluation Soil Structure (VESS) di Lahan Tambang Silika, Semak Belukar, Agroforestri, dan Hutan Tanaman: Visual Evaluation of Soil Structure (VESS) in Silica Mining Land, Shrubland, Agroforestry, and Plantation Forest - Putra, Fernanda Reza; Wasis, Basuki; Wijayanto, Nurheni (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Differences in land management affect the condition of land cover which has an impact on soil quality, especially soil structure. This research aims to analyze differences in the quality of visual soil structure (VESS) and its relationship with soil physical and chemical properties on silica mining land, shrubs, agroforestry, and plantation forests. Mining land has a poor soil structure, while agroforestry and plantation forest land has a good soil structure. This difference is influenced by vegetation factors and organic matter availability. VESS values were strongly correlated with fill weight and porosity, moisture content, soil pH, and soil C-organics. This research shows that the VESS method is a practical and efficient indicator for assessing soil quality.